2016
DOI: 10.1007/s10846-016-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Set-point Control of Mobile Robot with Obstacle Detection and Avoidance Using Navigation Function - Experimental Verification

Abstract: This paper presents the results of an experimental verification of mobile robot control algorithm including obstacle detection and avoidance. The controller is based on the navigation potential function that was proposed in work (Urakubo, Nonlinear Dyn. 1475-1487 2015). Conducted experiments considered the task of reaching and stabilization of robot in point. The navigation potential agregates information of robot position and orientation but also the repelling potentials of obstacles. The obstacle detection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Despite Binger et al and Ciullo reported theuseof IV robots for biomedical purposes [9,[31][32][33], they showed weight limitations and lacked the alarm system. Our robotic IV-pole was designed to overcome this limitation and was associated with an alarm system.…”
Section: Discussionmentioning
confidence: 99%
“…Despite Binger et al and Ciullo reported theuseof IV robots for biomedical purposes [9,[31][32][33], they showed weight limitations and lacked the alarm system. Our robotic IV-pole was designed to overcome this limitation and was associated with an alarm system.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are motivated by the research introduced by Khatib 5 for online collision avoidance using APFs. Examples of the analytical approach with an NF are presented in previous studies, 6 8 whose results originate from the NF definition introduced by Rimon and Koditschek. 4 With this approach, the NF is defined as a composition of several functions each designed to satisfy specific properties established by Rimon and Koditschek.…”
Section: Introductionmentioning
confidence: 96%
“…The author of this paper together with its co-authors conducted extensive tests of this algorithm including simulations for sphere worlds [10], star worlds [6], and experiments for sphere worlds [7][8][9].…”
Section: Introductionmentioning
confidence: 99%